2014
DOI: 10.1007/s00103-013-1906-z
|View full text |Cite
|
Sign up to set email alerts
|

Printmedien- und Internetangebote mit Informationen zur Darmkrebsfrüherkennung und ihre kriteriengestützte Bewertung aus Expertensicht

Abstract: In Germany, individuals who have statutory health insurance have free access to colorectal cancer (CRC) screening tests, and can choose between a fecal occult blood test and a screening colonoscopy. Evidence-based health information may support informed choices regarding whether or not to undergo CRC screening. The aim of this study was to assess whether the available German information materials on CRC screening meet evidence-based health information standards. A systematic search was made for print media and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
3
5
0
1
Order By: Relevance
“…The risks associated with cancer screening were either mentioned very little in the evaluated health information or not at all. This finding is consistent with the results of other studies [ 19 , 43 , 44 ]. Günster et al [ 43 ] pointed out that the existing information offerings on colorectal cancer screening are inadequate.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The risks associated with cancer screening were either mentioned very little in the evaluated health information or not at all. This finding is consistent with the results of other studies [ 19 , 43 , 44 ]. Günster et al [ 43 ] pointed out that the existing information offerings on colorectal cancer screening are inadequate.…”
Section: Discussionsupporting
confidence: 94%
“…In particular, they stated that information about the disadvantages of a colonoscopy (36%) was provided considerably less often than information about the benefits of the examination (75%) [ 43 ]. Dreier et al [ 19 ] highlighted an imbalance between the presentation of the benefits and the risk. Tian et al [ 44 ] identified also a lack of key information about risks and benefits by assessing web-based patient education materials in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that only half of the information materials maintain neutrality without downplaying or exaggerating benefits or risks. Nevertheless, this is more than the rate reported in a previous study of health information on colorectal cancer screening, in which merely 7% of the leaflets and one-third of the booklets and websites maintained neutrality [44]. We found two information materials that explicitly encourage the reader to undergo PSA testing and one that advises against the test.…”
Section: Discussionmentioning
confidence: 56%